Bioactive secondary metabolites from the deep-sea derived fungus Aspergillus sp. SCSIO 41029 - Chen, Weihao; Chen, Chunmei; Long, Jieyi; Lan, Sujuan; Lin, Xiuping; Liao, Shengrong; Yang, Bin; Zhou, Xuefeng; Wang, Junfeng; Liu, Yonghong (Journal of antibiotics, 2021)
Two new compounds classified as one new lumazine peptide, penilumamide K ( 1 ) and one new sesquiterpene ( 2 ), were obtained from the deep-sea derived fungus Aspergillus sp. SCSIO 41029, together with eleven known compounds ( 3 − 13 ). The structures of 1 − 13 including absolute configurations were determined by detailed NMR spectroscopy, HR-ESI-MS, chemical derivatization, and optical rotation data. Among them, compound 1 represents the first lumazine peptide reported from deep-sea derived fungus. The bioactive assay exhibited that compounds 1 , 3 , 4 , 5 , 7 and 10 had significant potency against α -glucosidase with IC 50 values ranging from 18.61 to 109.06 μΜ. In addition, compounds 4 and 9 showed strong antibacterial activity against Staphylococcus aureus with MIC values of 0.78 and 6.25 μg ml −1 , respectively.